Constitution, Constitutional Court and National Criminal Law - San Martín Castro, César (2008)
Within the framework of the State of Right, the Peruvian legal system always have to be interpreted according to the current Constitutional charter, because the fariness contents emerge there from the punitive norms that regulate the communicative processes of the Peruvian society in order not to generate defenselessness states, neither scopes of impunity. In the present work the brilliant national author sets out the constitutional principles of the Criminal Law and the way in which the Constitution allows the protected reading of the punitive norms.